Demo: Towards immersive and interactive gym exercises - RABBI, Fazlay (Institutional Knowledge at Singapore Management University, 2016)
We demonstrate JARVIS, a novel virtual coaching system based on virtual reality (VR) and Internet of Things (IoT) technologies. It creates a truly immersive gym exercising experience for machine-based strength training and guides users in a highly interactive manner. With these unique advantages, we believe that JARVIS has a potential to revolutionize personal fitness experiences.